2018
DOI: 10.2323/jgam.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and molecular characterization of an acidic and thermostable chitinase 1 from <i>Streptomyces thermodiastaticus</i> HF 3-3

Abstract: Chitinase 1 (Chi1) is an acidic and thermostable hydrolytic enzyme capable of the breakdown of chitin, a resilient biopolymer that is the primary building block of fungi cell walls and marine exoskeletons. In this study, Chi1 was purified from the bacterium Streptomyces thermodiastaticus HF 3-3, and its properties were carefully characterized. The molecular mass of Chi1 was estimated to be approximately 46 kDa and, through sequencing, its N-terminal amino acid sequence was identified as ADSGKVKL. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Organic solvents are used to solubilize hydrophobic substrates in enzymatic assays. The activity of purified CHI was also obviously increased by the presence of Tween 80, similar to chitinase from S. thermodiastaticus HF 3-3 (Take et al, 2018). This indicates that Tween 80 reduces the activation energy of the reaction, promoting the enzymatic reaction.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Organic solvents are used to solubilize hydrophobic substrates in enzymatic assays. The activity of purified CHI was also obviously increased by the presence of Tween 80, similar to chitinase from S. thermodiastaticus HF 3-3 (Take et al, 2018). This indicates that Tween 80 reduces the activation energy of the reaction, promoting the enzymatic reaction.…”
Section: Discussionmentioning
confidence: 72%
“…Chitinases can be subdivided into three families based on their structural motives: the glycoside hydrolase families 18, 19 and 20 (Take et al, 2018). Chitinases can be further classified as endochitinases, exochitinases, or N-acetylglucosaminases (NAGases) based on the mechanism of chitin hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…A 46kDa Chi1 was purified from Streptomyces thermodiastaticus HF 3-3 with specific activity of 2.4 U mg −1 . The enzyme was found to be remarkably stable over a wide range of pH, temperatures, and chemical exposures (Take et al, 2018 ). Moreover, thin-layer chromatography (TLC) analysis of CC cleavage products revealed that Chi1 exhibited endo- pattern of cleavage with the generation of (GlcNAc) 2 as the major product and minimal amounts of (GlcNAc) 3 and GlcNAc (Take et al, 2018 ).…”
Section: Strategies For Cos and Glcnac Productionmentioning
confidence: 99%
“…The enzyme was found to be remarkably stable over a wide range of pH, temperatures, and chemical exposures (Take et al, 2018 ). Moreover, thin-layer chromatography (TLC) analysis of CC cleavage products revealed that Chi1 exhibited endo- pattern of cleavage with the generation of (GlcNAc) 2 as the major product and minimal amounts of (GlcNAc) 3 and GlcNAc (Take et al, 2018 ). Extracellular chitinases production and its utilization for COS and GlcNAc conversion has also been extensively studied, and some findings have shown high potentiality in terms of catalytic efficiency and/or thermal and pH stability (Halder et al, 2019 ).…”
Section: Strategies For Cos and Glcnac Productionmentioning
confidence: 99%
“…The activity of purified CHI was also obviously increased by the presence of Tween 80, similar to chitinase from S. thermodiastaticus HF 3-3 (Take et al, 2018). This indicates that Tween 80 reduces the activation energy of the reaction, promoting the enzymatic reaction.…”
Section: Discussionmentioning
confidence: 72%